ANALISIS PERBANDINGAN RASIO KEUANGAN SEBELUM DAN SESUDAH PENERAPAN PSAK 73 PADA PT TELEKOMUNIKASI INDONESIA (PERSERO) Tbk - Shelma Sabrina; Auliffi Ermian Challen (JURNAL PUNDI, 2023)
PSAK 73 is the latest rental accounting standard adopted from IFRS 16. PSAK 73 is effective for 2020. Loan rental classification is a type of rental allowed in PSAK 73 where the recognition, measurement, presentation and disclosure of property rights become more detailed in the position report finance. This study aims to analyze the financial ratios at PT Telekomunikasi Indonesia (Persero) Tbk which has implemented PSAK 73. The research period used was 2019-2020. The data used is secondary data obtained from the IDX. This study uses a quantitative descriptive method to assess the company's financial performance before and after the implementation of PSAK 73. The results showed that there was a significant differences in the liquidity ratio that was projected with the current ratio, solvency ratios that were projected with debt to asset ratio and debt to equity ratio, and the ratio of activities with total asset turnover between 1 (one) year before with 1 (one) after the implementation of PSAK 73 and there was no significant difference in the profitability ratio that was projected with return on assets and return on equity between 1 (one) year before with 1 (one) years after the implementation of PSAK 73.